Criminal Legislation and Women in Sexual Assault Cases: Justice or Victim Blaming? - Abdelaziz, Dalia Kadry (Journal of Posthumanism, 2025)
Sexual assault is a critical social problem with extensive ramifications that deeply affect and displace models of women (Alfadhel, Fouda, & Awny, 2024). Not only does it have an impact on their physical and emotional health, but also on their sense of safety, autonomy, and ability to participate in society fully. This study offers a comparative analytical account of criminal legislation on sexual assault crimes because it intends to catch the actual role of such laws in the process of justice and the protection of the rights of women as victims or, on the contrary, in the blame they get from such crimes. It examines the relationship between legal provisions and societal culture and how, in turn, this affects the judiciary and society’s treatment of women who are the victims of such crimes. But the fact is that while criminal laws are meant to protect rights and uphold the dignity of human beings, most legal systems do not have adequate laws to protect victims and what they have is often victim blaming" (Independent Office for Police Conduct [IOPC], 2024) This research highlights the ways in which cultural and social factors can affect the enforcement of legal provisions, resulting in victim blaming rather than the delivery of justice. It also deals with the influence of these cultural factors upon judicial processes and damage to justice in crimes against women. This study also incorporates a comparative overview between Sharia Islamic law and some Western and international legal systems to identify some legislative and cultural gaps that could prevent the realization of justice. The research seeks to provide legal and social solutions to amend the prevailing conditions and to reinforce the legal protection of women through legal amendments. It also features social awareness mechanisms that support judicial neutrality and work toward the realization of justice.